2018
DOI: 10.1186/s12913-018-2955-7
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork in primary palliative care: general practitioners’ and specialised oncology nurses’ complementary competencies

Abstract: BackgroundGeneralists such as general practitioners and district nurses have been the main actors in community palliative care in Norway. Specialised oncology nurses with postgraduate palliative training are increasingly becoming involved. There is little research on their contribution. This study explores how general practitioners (GPs) and oncology nurses (ONs) experience their collaboration in primary palliative care.MethodsA qualitative focus group and interview study in rural Northern Norway, involving 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
(42 reference statements)
1
23
0
7
Order By: Relevance
“…For effective teamwork in specialist palliative care, leadership is crucial (Dahlin, Coyne, Goldberg, & Vaughan, ); however, defining and agreeing on what leadership comprises may be challenging. One reason for the focus on teamwork in palliative care is the potential for effectively combining diverse skills and perspectives to better meet the complex needs of patients and families facing life‐threatening illness and death (Ciemins, Brant, Kersten, Mullette, & Dickerson, ; Johansen & Ervik, ; Wagner, ). Gardner () has outlined the tasks of leadership as envisioning goals, affirming values, motivating, managing, achieving a workable unity, explaining, serving as a symbol, representing the group and renewing.…”
Section: Introductionmentioning
confidence: 99%
“…For effective teamwork in specialist palliative care, leadership is crucial (Dahlin, Coyne, Goldberg, & Vaughan, ); however, defining and agreeing on what leadership comprises may be challenging. One reason for the focus on teamwork in palliative care is the potential for effectively combining diverse skills and perspectives to better meet the complex needs of patients and families facing life‐threatening illness and death (Ciemins, Brant, Kersten, Mullette, & Dickerson, ; Johansen & Ervik, ; Wagner, ). Gardner () has outlined the tasks of leadership as envisioning goals, affirming values, motivating, managing, achieving a workable unity, explaining, serving as a symbol, representing the group and renewing.…”
Section: Introductionmentioning
confidence: 99%
“…We found that GPs were eager to recognize the older women as worthy human beings, but seemed to have reduced opportunities to do so, as well as less willingness to accomplish situations increasing the relative dignity -despite their duty to carry out home visits to patients incapable of traveling to the GP office (Regulations of the regular GP's scheme, 2012). Gallagher et al (2008) related GPs' limited awareness of the concept of dignity to staff attitudes and culture of care, whereas Johansen and Ervik (2018) drew attention to GPs' missing out of collective networks, learning primarily from individual-professional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, high quality end-of-life care for the rising number of older women with incurable cancer is now of great importance and should warrant sufficient healthcare resources, proper alleviation of symptoms, and respectful and supportive care (Cain & Denny, 2018;Rochon et al, 2020). This presupposes increasing demands on healthcare services and a multidisciplinary collaboration among healthcare professionals (HCPs) with complementary competencies to fulfil the complex needs of patients with incurable cancer (Johansen & Ervik, 2018).Figure 1 Despite the diversity in the term "older age" due to genetic inheritance and the environments in which older people live, we here define "old" from the age of 65 years in this study (WHO, 2020). Older people are often considered as a single group without taking account of gender differences, whereas care for older women requires an approach on aging, disease morbidity and treatment that is different from care for men (Gemmati et al, 2019;Rochon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study is to explore the challenges faced by nurses in providing palliative cancer care in the northernmost part of Norway. There have been few studies in Norway of this particular nursing context (18,19), but more studies have been conducted in Canada, the USA and Australia on nurses' working conditions in rural palliative care (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%